Gestión del talento humano y su incidencia en la atención al cliente de la corporación nacional de telecomunicaciones – Cnt, Cantón Quevedo. - Rodríguez Ibarra, Yuri Margoth (2015)
The objective of this project is to work to improve diagnosis of human talent management customer service, for staff of the National Telecommunications Corporation CNT, Quevedo Canton. The issue focuses on the customer service department; as users do not respond adequately to all the requirements that apply when they come to this body, for this reason, a review of staff who is in charge of the customer is necessary. The methodology used for this research is qualitative and quantitative, since research methods such as observation, inductive, deductive were used. Information gathering techniques were applied as the interview the manager of the company and employee survey, the results were analyzed using statistical tables and charts that allow verification of the hypothesis. From the results we can highlight the answers mostly staff of the company known plans to improve care and customer service, there is difficulty in the digital system and this slows the process to this is taking solutions from training, motivation and commitment to the role and service offered by the company CNT, Quevedo.